THE EXISTENCE OF LEGEND AND THE VALUE OF CHARACTER EDUCATION OF THE THREE LAKES OF WEST SUMATRA (TWIN LAKES, MANINJAU LAKES AND SINGKARAK LAKES) (A STUDY OF LITERARY TOURISM) - Elen Inderasari; Danang Wahyu Triantoro; Fajri Syafiah (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2023)
West Sumatra has many tourist destinations that are widely known and travelled by the wider community. Many of the many tourist destinations stem from the power of oral literature in the form of legends. The famous lake tours in West Sumatra are the Twin Lakes, Maninjau Lake, and Singkarak Lake. These three lakes are beautiful tourist attractions, are known to many people, and contain local wisdom values wrapped in folklore, so that the Minangkabau people believe that they are true stories from their ancestors. The presence of folklore in the form of legends is used by the local community as an effort to preserve the tourist attractions of the three lakes with various versions of the story. Each legend contains the value of character education. Therefore, in addition to being a tourist attraction, the three lakes are also used as a medium for character education for the surrounding community. Thus, this study aims to describe the efforts to preserve the three lakes in West Sumatra through literary legend tourism and the value of character education contained in the three lake legends in West Sumatra. This study uses a qualitative description method with an interdisciplinary approach, using tourism studies and character education with the study of legend literature in balance with describing various activities in the preservation of tourism literature. The data and data sources are the stories of three legends of Twin Lakes: Maninjau Lake, Singkarak Lake, and Maninjau Lake; data collection techniques with documents and video observations. To test the wetness of the data, they used theoretical triangulation techniques and source triangulation. Then the data was analyzed using Miles and Hubberman.The results of this study indicate that efforts to preserve three lakes, namely Twin Lakes, Lake Maninjau, and Lake Singkarak in West Sumatra in legend literature and tourism, are carried out through various traditional ceremonies in each lake, such as the balimau tradition ceremony, the maninjau rakik tradition, the biduak race, and the implementation of the West Sumatra cultural festival as part of the management of culture and tourism. While the value of character education is contained in the three legends of the lake in West Sumatra as a form of advice from the ancestors, in the form of realizing mistakes, caring, praying, being responsible, diligent, and listening to advice